TINJAUAN AKADEMIS TENTANG ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Abdul Hijar Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Receipts from all legitimate sources must be properly recorded by the officer. Included in receipts are all monetary benefits in the form of commissions, rebates, discounts and interest as a result of the sale and/or procurement of goods and/or services and from the storage and/or placement of regional money. This revenue must be recorded as regional income and budgeted in the APBD. APBD expenditures must be based on a decree of authorization by the authorized official. An ideal pattern of relationship between the legislature and the executive should be established in the sense that there is a balance between the two institutions. The more democratic the political system, the more balanced the relationship between the legislature and the executive will be. The Regional Government and DPRD, especially for DPRD members who are directly involved in the regional financial budgeting process, can provide education and training related to regional financial budgeting that can increase their competence and expertise and provide additional new knowledge so that the planning process to determining APBD can run optimally and produce APBD quality in accordance with the expectations, needs and aspirations of the community.